Simple Maternity Search with Bayesian Networks - Andrade, M. A. P.; Ferreira, M. A. M. (EasyChair Preprint Nº 9970, 2025)
DNA profiles are commonly used in forensic identification problems. It was in England, in 1995, that the first DNA profiles databases were built. They gave rise to new challenges concerning the forensic identification. In this paper it is intended to exemplify how to use the analysis of DNA profiles to solve the problem of simple maternity search. For it it is necessary to make use of a probabilistic expert system (PES), in this case an object-oriented Bayesian network (OOBN).